AI public relations: the early rise of Kizuna AI - Nadra Ideyani Vita; Vincent E. Encluna; Nina Siti Salmaniah Siregar; Ana Rusmardiana; Samuel P.D. Anantadjaya (Jurnal Studi Komunikasi, 2023)
AI has assumed a dominant role in society, leveraging various tools to extend its influence beyond digital marketing and content creation. In the year 2023, AI's industry role has witnessed significant expansion. An illustrative example of this is the emergence of Kizuna AI, which serves as a testament to the fact that AI is not confined solely to scientific rigour but also encompasses creative endeavours akin to those undertaken by humans. In light of these developments, the New Media Theory prompts us to reconsider the discourse surrounding AI, recognising that it manifests differently in certain respects and has the potential to behave unpredictably as it becomes increasingly integrated into society. For this study, the Media Analysis model proposed by Neuman was employed to gain valuable insights. This research underscores the importance of fostering greater collaboration between humanity and scientific disciplines to gain a comprehensive understanding of how AI operates. By bridging these domains, researchers can unlock more profound insights into the workings of AI and its implications for society.